Answer:
For the last three years, the National Post has greeted the yuletide season by publishing the video above. With a simple message of maximizing charitable giving by donating money to the food bank instead of canned goods, it is one of our most popular videos of all time, reaching virtually every corner of the English-speaking world.
Step-by-step explanation:
Answer:
1. 469 2. 171 3. 36 4. 0 5. 60
Answer:
f(x) = ![2^{(3x)}](https://tex.z-dn.net/?f=2%5E%7B%283x%29%7D)
Step-by-step explanation:
The given options are,
a) f(x) = ![2^{(3x)}](https://tex.z-dn.net/?f=2%5E%7B%283x%29%7D)
b) f(x) = ![({\frac {1}{2}})^{3x}](https://tex.z-dn.net/?f=%28%7B%5Cfrac%20%7B1%7D%7B2%7D%7D%29%5E%7B3x%7D)
c) f(x) = ![2 \times ({\frac {1}{3}})^{x}](https://tex.z-dn.net/?f=2%20%5Ctimes%20%28%7B%5Cfrac%20%7B1%7D%7B3%7D%7D%29%5E%7Bx%7D)
d) f(x) = ![\frac {1}{2} \times ({\frac {1}{3}})^{x}](https://tex.z-dn.net/?f=%5Cfrac%20%7B1%7D%7B2%7D%20%5Ctimes%20%28%7B%5Cfrac%20%7B1%7D%7B3%7D%7D%29%5E%7Bx%7D)
Now, among the given options only option (a) satisfies the criteria stated in the question i. e.,
1. f(x) → 0 as x → - ∞ and
2 f(0) = 1
so, the correct answer is,
f(x) = ![2^{(3x)}](https://tex.z-dn.net/?f=2%5E%7B%283x%29%7D)
Y=6x (1)
y=5x-7 (2)
Substitute y into (2)
(6x)=5x-7 -- subtract 5x from both sides
x=-7
Sub x into 1
y=6(-7)
y=-42
x=-7
y=-42